2016
DOI: 10.5056/jnm15082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Enteric Neurons of Small Intestine in a Rat Model of Irritable Bowel Syndrome with Diarrhea

Abstract: Background/AimsPhysical and/or emotional stresses are important factors in the exacerbation of symptoms in irritable bowel syndrome (IBS). Several lines of evidence support that a major impact of stress on the gastrointestinal tract occurs via the enteric nervous system. We aimed to evaluate histological changes in the submucosal plexus (SMP) and myenteric plexus (MP) of the distal ileum in concert with the intestinal motor function in a rat model of IBS with diarrhea. MethodsThe rat model was induced by heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…A previous study has suggested that reduced proportion of nitrergic enteric neurons in the MP of the distal ileum contributes to the intestinal dysmotility observed in IBS. 31 However, our findings further demonstrate that intestinal dysmotility in IBS is also related to the hyperfunction of cholinergic neurons in the colonic MP. One potential explanation may be that chronic stress directly regulates the cholinergic system in ICCs and ENS via the brain-gut axis through key alterations in the expression and function of CHT1.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A previous study has suggested that reduced proportion of nitrergic enteric neurons in the MP of the distal ileum contributes to the intestinal dysmotility observed in IBS. 31 However, our findings further demonstrate that intestinal dysmotility in IBS is also related to the hyperfunction of cholinergic neurons in the colonic MP. One potential explanation may be that chronic stress directly regulates the cholinergic system in ICCs and ENS via the brain-gut axis through key alterations in the expression and function of CHT1.…”
Section: Discussionsupporting
confidence: 48%
“…44 In addition, NOdependent neurotransmission can exert inhibitory function on the GI contractility to counteract the effects of the cholinergic system. 31 All of these facts suggest a complex role for CHT1 in the regulation of GI motility in IBS. More recently, a study demonstrated that CHT1 also regulates the enzyme activity of enhanced mucosal acetylcholinesterase and influences the release of ACh by affecting the mobilization of vesicle pools, in addition to serving as the choline transporter.…”
Section: Discussionmentioning
confidence: 99%
“…30 Alterations in the structure and composition of the ENS have also been found in adult male rats exposed to 28 days of heterotypic chronic and acute stress which exhibit an increase in cholinergic and VIPergic neurons in ileal submucosal plexus, while in the myenteric plexus, the number of NOS-positive neurons is decreased. 31 In this issue, Medland et al 7 add to the existing literature by demonstrating for the first time using EWS that this effect is reproducible and longlasting in a larger mammalian species (pigs) which has translational relevance for humans. 8 Additionally, they show that there is a sex-specific hypersensitivity of secretomotor neuron function and upregulation of the cholinergic ENS which occurs in females exclusively.…”
Section: Influence Of Stress On Ens Structure Development and Functionmentioning
confidence: 99%
“…Remarkably, early life emotional distress (e.g., maternal separation model) and adult stress (e.g. water immersion in rodents) can also cause long-term changes in enteric glia and neurons, as well as changes in colon and gastric function in ways that may be relevant for gastroparesis and IBS (Bian et al, 2011; Fujikawa et al, 2015; Li et al, 2015; Moloney et al, 2015; Tominaga et al, 2016). Non-genetic factors may also protect the ENS from injury.…”
Section: Non-hscr Motility Disordersmentioning
confidence: 99%